2023
DOI: 10.1177/02654075221149955
|View full text |Cite
|
Sign up to set email alerts
|

From Close to Ghost: Examining the Relationship Between the Need for Closure, Intentions to Ghost, and Reactions to Being Ghosted

Abstract: Ghosting—the act of ending a relationship by ceasing communication without explanation—is a type of ostracism that threatens a person’s basic psychological needs for belonging, self-esteem, meaningful existence, and control. The experience of ghosting creates uncertainty within the relationship and may vary based on individual differences in the need for closure, which is the desire to avoid ambiguity. Across three preregistered studies with emerging adults, we predicted that a greater need for closure would b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 62 publications
0
6
1
Order By: Relevance
“…According to new research based on interviews with ghosters and ghostees [ 5 , 6 ], ghosting can also occur in platonic friendships. This contradicts earlier claims of researchers such as LeFebvre and Koessler [ 7 , 8 ], who restricted the term to romantic relationships.…”
Section: Introductioncontrasting
confidence: 65%
See 1 more Smart Citation
“…According to new research based on interviews with ghosters and ghostees [ 5 , 6 ], ghosting can also occur in platonic friendships. This contradicts earlier claims of researchers such as LeFebvre and Koessler [ 7 , 8 ], who restricted the term to romantic relationships.…”
Section: Introductioncontrasting
confidence: 65%
“…According to attachment theory, an infant’s early inability to bond with parental figures lies at the root of attachment avoidance in adulthood; ghosting can be understood in this context [ 18 ]. Avoidance of potentially stressful situations is considered to be a mechanism of defense that serves to shore up a fragile self-image [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Di Santo et al (2022) found that both sociosexual orientation and extraversion were positively associated with ghosting others. Finally, Leckfor et al (2023) found that in contrast to their expectations, the need for closure did not predict a lower intent to ghost, but instead showed a small positive correlation.…”
Section: Introductionmentioning
confidence: 84%
“…The piece outlines the impact of "ghosting" at all stages of the research process and what this means for the state of research overall as we move into the future. Ghosting is ending a relationship by stopping communication without explanation (Leckfor et al, 2023). Research has shown that the act of ghosting can have a negative psychological impact on the receiver of ghosting, including a hit to one's self-image and sense of belonging (Leckfor et al, 2023;Navarro et al, 2020).…”
mentioning
confidence: 99%
“…Ghosting is ending a relationship by stopping communication without explanation (Leckfor et al, 2023). Research has shown that the act of ghosting can have a negative psychological impact on the receiver of ghosting, including a hit to one's self-image and sense of belonging (Leckfor et al, 2023;Navarro et al, 2020). While we often refer to ghosting when it comes to more informal social relationships (e.g., dating, friendships), this type of behavior not only exists but has become amplified in the research world.…”
mentioning
confidence: 99%